Sustainable medium‐strength concrete (CS‐concrete) from colliery spoil in South Wales UK - Kinuthia, John; Snelson, David; Gailius, Albinas (Journal of Civil Engineering and Management, 2009)
This paper reviews one way in which colliery spoil can be utilized in low‐strength concrete. Colliery Spoil (CS) (minestone), a by‐product of coal mining, is abundant in most parts of the world. It has potential as a construction material but it has not been fully appreciated. This is partly because colliery spoil is not easy to utilize, due a number of drawbacks. The major problems identified in attempts to utilize CS in construction include excessive wear, expansive behaviour, leaching of heavy metals and even radioactivity. Thus, to date, the bulk of the CS utilization is limited to isolated cases of highway embankments, backfilling of mines, quarries and other surface tips, or in extreme cases subjected to marine and other disposal. This paper reports on the scope of technological benefits of utilizing colliery spoil (CS) in low to medium strength concrete. There has been intermittent pursuance of the benefits of utilizing colliery spoil in the United Kingdom. However, there is still no well‐accepted and/or positive feedback on any colliery‐based technology and/or construction material, apart from that relating its use for bulk fill. This research was triggered by proximity of large supplies of both CS and slag in South Wales, UK, as well as the authors’ interest in advances in sustainable construction. Two fractions of colliery spoil were mixed in equal proportions and used for concrete where the binder was PC, or novel binders comprising of either Wastepaper Sludge Ash (WSA) or WSA combined in equal proportions with Ground Granulated Blastfurnace Slag (GGBS), themselves industrial wastes or by‐product materials. Compressive strength of compacted cube specimens was monitored for a period of up to 56 days of curing. Results indicate that the performance of systems incorporating CS and WSA were of very poor workability, but the resultant strength was within the low to medium category usable for blinding concrete and or for use in bound granular fill or foundations.SantraukaAnglies kasyklų atliekos yra potenciali ekologiška žaliava statybos dirbiniams gaminti, tačiau iki šiol neištirtos jos savybės ir naudojimo galimybės. Staripsnyje pateikti tyrimų rezultatai rodo, kaip, taikant specialias technologijas, savybes modifikuojančius priedus, kompozicines rišamąsias medžiagas, galima anglies kasyklų atliekas naudoti vidutinio stiprumo tvariam betonui gaminti.First Published Online: 14 Oct 2010Reikšminiai žodžiai: betonas, anglies kasyklų atliekos, stabilizatoriai, plastikliai, popieriaus atliekų šlamo pelenai.